PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR MENGGUNAKAN MODEL NUMBERED HEADS TOGETHER - Murni, Anita Dwi; Arwin, Arwin; Mansur, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract The purpose of this research was to describe the improvement of integrated thematic learning outcomes using the Numbered Heads Together (NHT) type cooperative model at 4th grade of elementry school in Garegeh of Bukittinggi. The research subjects were teachers and 26 students.  Research site in Garegeh of Bukittinggi. The result showed an increase in : a)RPP cycle I 83,33% (good) and cycle II 91,67% (very good) b)implementation in the aspects of teacher cycle I 81,24% (good) and cycle II 94,44% (very good) c) aseesment of the result of student alignment with the average in cycle I 68,77 and cycle II with an average of 79,10. Based on these results it can be concluded that the numbered heads together (NHT) of cooperative model can improve integrated thematic learning outcomes in students.  Keyword: numbered Heads Together model,learning outcomes